(untitled) (Al-Farooq Journal of Sciences, 2026)
The study aimed to explore the current application of strategic management in developing the marketing performance at the Faculty of Economics and Political Science, University of Tripoli, Section B. The researchers adopted a descriptive-analytical approach to collect, classify, and analyze the data. The study population consisted of faculty members and administrative staff of the college, and 48 questionnaires were distributed to the study sample. The findings revealed a positive correlation and a statistically significant direct role of strategic management in enhancing marketing performance. The study recommended strengthening strategic monitoring and evaluation systems by developing clear marketing performance indicators to ensure the measurement of strategy outcomes and timely correction of deviations.